The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fneur.2020.00643
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Objective Cardiometabolic Burden Associated With Attenuations in the P3b Event-Related Potential Component in Older Adults

Abstract: Cardiometabolic diseases and risk factors increase the risk of late-life cognitive impairment and dementia and have also been associated with detrimental gray and white matter changes. However, the functional brain changes associated with cardiometabolic health in late-life are unclear. We sought to characterize these functional changes by recording event-related potentials (ERPs) during an n-back working memory task (0, 1, and 2 back) in 85 adults (60% female) between 50 and 80 years of age. Due to a stratifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…Additionally, the majority (>90%) of the obese individuals reported cardiometabolic disease comorbidities such as diabetes and hypertension. This finding backs up earlier studies that showed a link between a higher BMI and an increased risk of hypertension and diabetes, with the risk peaking between the ages of 18 and 53 [50]. Previous research found that age and metabolic disorder, both independently and in combination, may increase the risk for cognitive decline in obese individuals, especially in midlife [51].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, the majority (>90%) of the obese individuals reported cardiometabolic disease comorbidities such as diabetes and hypertension. This finding backs up earlier studies that showed a link between a higher BMI and an increased risk of hypertension and diabetes, with the risk peaking between the ages of 18 and 53 [50]. Previous research found that age and metabolic disorder, both independently and in combination, may increase the risk for cognitive decline in obese individuals, especially in midlife [51].…”
Section: Discussionsupporting
confidence: 82%
“…Participants were recruited as part of a larger study investigating the neurophysiological and lifestyle changes across mid to late life. Other results using task-based EEG and dietary measures are published elsewhere (Keage et al, 2020;Wade et al, 2020). The study was approved by the University of South Australia Human Ethics Committee (0000034635).…”
Section: Participantsmentioning
confidence: 99%
“…These differences, as well as a slowing of alpha peak frequency, were seen in individuals with Alzheimer’s Disease, and to a lesser extent for MCI (Babiloni et al, 2013; Meghdadi et al, 2021; Vecchio et al, 2013). We have also demonstrated that the P3b event-related potential (ERP) component recorded during an n-back memory task is reduced in older adults with increased cardiometabolic burden (Keage et al, 2020). Taken together, this evidence suggests that there are partially overlapping EEG correlates of increased age, cognitive decline and cardiometabolic burden.…”
Section: Introductionmentioning
confidence: 99%